Partial fishmeal replacement by mussel meal or meat and bone meal in low‐fishmeal diets for juvenile Ussuri catfish (Pseudobagrus ussuriensis): Growth, digestibility, antioxidant capacity and IGF‐I gene expression. (18th December 2019) - Wang, Yi; Tao, Shengqiang; Liao, Yilu; Lian, Xuqiu; Luo, Chengzeng; Zhang, Ying; Yang, Chenghui; Cui, Cunhe; Yang, Jiaming; Yang, Yuhong
Abstract: This study evaluated the effects of replacing fishmeal with mussel meal or meat and bone meal in low‐FM diet on growth performance, body composition, digestibility, antioxidant capacity and IGF‐I gene expression in juvenile Ussuri catfish ( Pseudobagrus ussuriensis ). The results showed that no significant changes in SGR, FE and PER were observed between MM40 and LFM groups, but significantly reduced result was found in MBM40 group. MM40 group showed the higher ADC of lipid (93.30%) and lipase activity (95.00 U/gprot) than LFM group (90.97%; 70.18 U/gprot). MM40 or MBM40 diets led to significant reduction of SOD and CAT activities. MM40 group showed significantly higher MDA level (5.84 nmol/mg) than LFM group (4.73 nmol/mg). The activities of LZM decreased significantly in MM40 and MBM40 groups compared with LFM group. MM40 and MBM40 groups showed no significant difference in hepatic IGF‐I gene expression levels compared with LFM group. The findings demonstrated that MM could substitute 400 g/kg of FM in low‐FM diet for Ussuri catfish without influencing the growth, but to some extent, spontaneous oxidative stress and immune damage could occur; when 400 g/kg of FM was replaced by MBM, significantly negative effects were observed on growth, antioxidant capacity and non‐specific immune response of Ussuri catfish.